2018
DOI: 10.1039/c7fo01548h
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of glucono-δ-lactone attenuates skin inflammation and contributes to maintaining skin condition

Abstract: Skin properties are influenced by both external (e.g., ultraviolet [UV], chemicals, and bacteria) and internal factors (e.g., nutrition and hormones). Therefore, some dietary supplements are expected to improve skin conditions. Glucono-δ-lactone (GDL) is widely used as a food additive and is naturally present in wine, honey, and other foods. The aim of this study was to assess whether GDL improves skin condition and inflammation. In a double-blind, placebo-controlled study, 40 healthy Japanese male volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Therefore, dietary GDL could improve skin barrier function, elasticity, and viscoelasticity. Comparing the results of our own study with those above on the use of oral GLA, we can conclude that topical GLA has a moisturizing effect on the most superficial layers of the skin (reducing TEWL) and oral GLA has a stronger effect on strengthening the layers of the dermis by improving the viscoelasticity of the skin by improving the quality of the interstitial fluid throughout the fibrous network 13 …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, dietary GDL could improve skin barrier function, elasticity, and viscoelasticity. Comparing the results of our own study with those above on the use of oral GLA, we can conclude that topical GLA has a moisturizing effect on the most superficial layers of the skin (reducing TEWL) and oral GLA has a stronger effect on strengthening the layers of the dermis by improving the viscoelasticity of the skin by improving the quality of the interstitial fluid throughout the fibrous network 13 …”
Section: Discussionsupporting
confidence: 69%
“…skin (reducing TEWL) and oral GLA has a stronger effect on strengthening the layers of the dermis by improving the viscoelasticity of the skin by improving the quality of the interstitial fluid throughout the fibrous network. 13 In skin care processes, it should also be borne in mind that the acidic pH of the skin's mantle affects the proper course of physiological processes, such as lipid barrier formation and stratum corneum homeostasis (pH-dependent enzyme work, exfoliation, and antimicrobial defense). Proper pH regulation is necessary to prevent infections and reduce the susceptibility of the skin to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, because UVC is almost completely absorbed by the ozone layer and atmosphere, UVB is the most damaging electromagnetic radiation. Several studies have reported the harmful effects of UVB on skin, such as skin photoaging [ 14 , 15 , 16 ], DNA damage and increased oxidative stress [ 17 , 18 ], and skin inflammation through various mechanisms [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, choline (PubChem ID: 305) which is the Top 10 Metabolite from pinang yaki extract (ESI+) has also been widely researched for its effects in preventing SARS Cov-2 Infection and has good neuroprotective immunity (Chowdhury & Pathak., 2020). Other contents in pinang yaki (Areca vestiaria) such as Benzothiazole (PubChem ID: 7222) (Ali & Siddiqui., 2013), L-Isoleucine (PubChem ID: 6306) (Mao et al, 2018), D-Glucono-Delta-Lactone (PubChem ID: 736) (Kuwano et al, 2018) The above compounds have been identified as contained in pinang yaki extract, which shows its potential as a Covid-19 antiviral herbal supplement product. Of course, it needs further study, researchers will conduct an in vivo study to find out the effect of pinang yaki extract as an antiviral herbal supplement Covid-19 (based on the results of the compounds or metabolomic profiling in this paper).…”
Section: Discussionmentioning
confidence: 99%